Effect of Oat β- glucan as a Fat Replacer on Physicochemical, Rheological and Sensory Properties of low-fat Sheep Milk Yoghurt - Shno S. Mohammed; Jasim M. S. Al-Saadi; Rahela S. Qader; Hanan F. Khalil (Zanco Journal of Pure and Applied Sciences, 2025)
The notion of yoghurt's positive impact on human health and nutrition has been widely held throughout several civilizations for a considerable duration. The aim of this study is to examine the benefits of adding oat beta glucan to skim milk in order to enhance the production of yogurt. An investigation was conducted on yogurt samples to analyze their physicochemical properties (pH, titratable acidity, syneresis, water-holding capacity (WHC), and hardness) as well as their sensory qualities. The samples were stored at a temperature of 4±1 °C for 1, 7, 14, and 21 days. The analysis revealed that the average pH value of both types of sheep milk samples was within the range of 6.6 to 6.5, indicating that the acidity level was within the usual range for all milk compositions. The yoghurt samples had the maximum acidity at beta glucan concentrations of 0.75% and 1%. The study is shown that the addition of oat β-glucan, particularly at a concentration of 0.25%, enhances the qualitative characteristics of low-fat yogurt and increases sensory evaluation ratings when compared to control treatments.